Taxonomic Study of the Genus Heptapleurum Gaertn. (Araliaceae) in Sarawak - Norazira, Ramnor (Universiti Malaysia Sarawak, 2024)
Heptapleurum Gaertn. is a genus that belongs to the Araliaceae family. Previously, all the species in this genus were placed under the Asian Schefflera J. R. Forst. & G. Forst.. After transferring all the species, the genus is now known as the largest genus in Araliaceae and can be found at tropical and subtropical of Asia and on several islands and archipelagos of the western Pacific. There are some studies of Heptapleurum that have been done in other regions. However, the information on the species in is still lacking and poorly understood in Sarawak. Therefore, the objectives of this study were to determine the number of Heptapleurum taxa in Sarawak, to construct a taxonomic key of Heptapleurum taxa in Sarawak, to describe all the Heptapleurum taxa in Sarawak based on the herbarium specimens and to make a distribution map of Heptapleurum taxa in Sarawak. The observation and measurements of both vegetative and reproductive parts were made from the herbarium specimens from Sarawak Herbarium (SAR) and Unimas. A distribution map was created by using ArcMap 10.3. Based on the observations of all 583 specimens, there are 73 Heptapleurum taxa in Sarawak. Out of 73 taxa, 25 taxa are published species, 27 taxa are unpublished and 21 are imperfectly known taxa. The distribution map, taxonomic key and description of all Heptapleurum taxa in Sarawak are presented here in this study. The genus can be found throughout Sarawak in various types of habitat with elevational ranges from near sea level up to the highest peak in Sarawak which is 2424 m on Mount Murud. From this study, it is concluded that there are still many undiscovered and unidentified taxa of Heptapleurum in Sarawak. Further study about this genus in Sarawak is much needed to improve the knowledge of this challenging genus.